Policy Steps to Address the Corona Crisis. (Policy Papers; Policy Paper ;, 2020)
Monitoring, containing and mitigating the effects of the corona virus are top priorities. Timely and decisive actions by health authorities, central banks, fiscal, regulatory and supervisory authorities can help contain the virus outbreak and offset the economic impact of the pandemic. Central banks must support demand and confidence by preventing a tightening of financial conditions, lowering borrowing costs for households and firms, and ensuring market liquidity. Fiscal policy must step up to provide sizable support to the most affected people and firms, including in hard-to-reach informal sectors. Regulatory and supervisory responses must aim to preserve financial stability and banking system soundness while sustaining economic activity.